A review on optimization of vehicle frontal crashworthiness for passenger safety - Ahmed Khatri, Naveed; Shaikh, Humaiz; Ahmed Mahir, Zulfikar; Shah, Asadullah; Ahmed, Syed Faiz (Science Publishing Corporation Inc, 2018)
In engineering and technology safety of human life has always been a top priority. With the increasing usage of vehicles in everyday life, probability of deaths and injuries has also increased. This paper provides a critical review on the optimization of vehicle frontal crashworthiness studied by researchers using various methods. They investigated the effects of crash at a defined speed using the method of FRB and ODB impact. It further discusses other methods that can be used to save passengers’ life. Also, the designing and manufacturing limitations faced by engineers in actual development processes. Finally, it is concluded that improved structure design and material composition can significantly increase the overall crashworthiness of the vehicle.